Foreign exchange option pricing : a practitioner's guide - Clark, Iain J. (Chichester, West Sussex, U.K. : Wiley, 2011)
It is a practitioner's guide to the latest, cutting edge option pricing formula for foreign exchange. It contains everything a trader working in a bank or hedge fund would need to know about the mathematics of foreign exchange.
A gentle introduction to FX markets -- Mathematical preliminaries -- Deltas and market conventions -- Volatility surface construction -- Local volatility and implied volatility.
Includes bibliographical references (p. [265]-270) and index.
opc 09/05/13
Loans
Keywords: Options (Finance) -- Prices; Stock options; Foreign exchange rates